Review of the Iranian species of Pachylaelapidae, with description of a new species of Onchodellus (Acari: Mesostigmata) - Ahadiyat, Ali; Moghadam, Sahebeh Ghasemi; Kermani, Reyhaneh Abutaleb; Joharchi, Omid (Zootaxa, 2020)
A new pachylaelapid mite species of the genus Onchodellus, O. masani sp. nov., is described and illustrated based on female specimens from Iran. The new species is compared with congeneric species with shortened peritremes. The new regional distributions for three examined species, Onchodellus hispani (Berlese), O. karawaiewi (Berlese), and O. strigifer (Berlese) are presented, and the situation of other species of the genus in Iran is revised. The current knowledge of the pachylaelapid species of Iran is discussed and a new list of the described and recorded species of the family is provided.